Langkah-langkah Pelaksanaan Sistem Penjaminan Mutu Dalam Dunia Pendidikan - Aisi, Okta Khusna (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
The quality assurance system of education is needed right now, considering education quality of Indonesia is still low compared by developed countries. The aim of this study is to determine the steps need to be done to implement the quality assurance system of education.Â  From the literature review finally obtained the conclusion that the steps to implement the quality assurance system of education are: preparing the quality assurance program, choosing the data collection instrument, collecting and verifying data, processing and analyzing data, reporting data-based findings, using findings for standard achievement verification, choosing priority needs for quality improvement, developing programs and budget quality improvement, implementing quality improvement program, monitoring quality improvement activities, reporting quality improvement results, carrying out suggestions for the next phase of improvement.Keywords: langkah-langkah, sistem penjaminan mutu, pendidikan.